Does green innovative practices matter? The effect of green innovation on green entrepreneurship sustainability. - Mathushan, P.; Pushpanathan, A. (Faculty of Management Studies and Commerce, University of Jaffna., 2020)
Green entrepreneurs have been realized as critical motorists for a transition to a green economy. There has been a growing interest in developing a ‘green’ economy as a means of reconciling economic development and the environment. Hence, green entrepreneurs are exchanging fluctuating stiffnesses between their business activities, environmental philosophies, and broader contexts at the intertwine between the green economy and the mainstream economy. However, research on green innovation and green entrepreneurship has been finite focused and remained agnostic in Sri Lankan context. More specifically, entrepreneurs in Vavuniya district rigorously encountering colossal problems in green innovation (e.g. green packing, green marketing). In fact, there is an urge to foster green innovative practices to reap business success. Hence, the researchers selected entrepreneurs in Vavuniya district. Therefore, the present study aims to investigate the effect of green innovation (innovative practices) on green entrepreneurship sustainability. Data were gleaned from purposively chosen entrepreneurs in Vavuniya district with in-depth interviews. The results revealed that most informants disclosed that entrepreneurs do not appear to be prepared to encounter the challenges or take unforeseen risks by capitalizing in green business and green innovative practices. Ironically the government and other departments and educational institutions (colleges and universities) do not recognize their role and fail to support green entrepreneurship development.
Keywords: Green entrepreneurs.; Green entrepreneurship sustainability.; Green innovative practices.; Sustainability.